2006
DOI: 10.1016/j.foodchem.2005.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Glucose oxidase effect on dough rheology and bread quality: A study from macroscopic to molecular level

Abstract: Enzymes are used in baking to improve dough handling properties and the quality of baked products. Glucose oxidase (GO) is an enzyme with oxidazing effect due to the hydrogen peroxide released from its catalytic reaction. In this study, the macroscopic effect of increasing glucose oxidase concentrations on wheat dough rheology, fresh bread characteristics and its shelf life during storage was determined. A reinforcement or strengthening of wheat dough and an improvement of bread quality can be obtained with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 23 publications
9
98
0
9
Order By: Relevance
“…The oxidant action of GOD led to a cross-link among proteins through disulfide and non-disulfide bonds into the gluten network, forming large protein aggregates (Steffolani et al 2010). These results are in agreement with various studies (Primo-Martin et al 2005;Bonet et al 2006;Dagdelen and Gocmen 2007b) which reported that glucose oxidase effect on j). However, the binary combinations (Mix 6) of glucose oxidase and ascorbic acid significantly increased the deformation energy levels (340.10 −4 J) indicating a positive interaction between the two oxidant additives.…”
Section: Dough Propertiessupporting
confidence: 90%
See 2 more Smart Citations
“…The oxidant action of GOD led to a cross-link among proteins through disulfide and non-disulfide bonds into the gluten network, forming large protein aggregates (Steffolani et al 2010). These results are in agreement with various studies (Primo-Martin et al 2005;Bonet et al 2006;Dagdelen and Gocmen 2007b) which reported that glucose oxidase effect on j). However, the binary combinations (Mix 6) of glucose oxidase and ascorbic acid significantly increased the deformation energy levels (340.10 −4 J) indicating a positive interaction between the two oxidant additives.…”
Section: Dough Propertiessupporting
confidence: 90%
“…Enzyme levels were selected according to several bibliographical reports (Rasiah et al 2005;Bonet et al 2006;Caballero et al 2007a, b;Steffolani et al 2010). …”
Section: Experimental Mixture Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Katina et al (2006) apresentaram valor de 4,1 cm 3 .g -1 para o volume específico de pães de fôrma com alto teor de fibras e com adição de misturas de enzimas. Bonet et al (2006) relataram volumes específicos variando de 3,41 a 4,42 cm 3 .g -1 em pães adicionados de glicose oxidase.…”
Section: Análise Sensorialunclassified
“…Apesar de inúmeras pesquisas comprovarem que a adição de alfa-amilase provoca um aumento no volume específico de pães (BONET et al, 2006), no presente estudo, para as formulações onde houve adição de 10ppm e 50ppm de enzima (F2 e F4), este fenômeno não foi observado. Este resultado pode ser explicado pela presença das fibras, já que sua adição em produtos de panificação é comumente relacionada a falhas no processo, como amargor e redução de volume (BERRY, 2004).…”
Section: Resultsunclassified